A Shared Value Strategy in Cooperative Enterprises: The Role of Humanistic Governance - Basbeth, Firdaus (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Cooperatives, as social enterprises, prioritize community welfare and shared value over profit maximization. This study contributes a novel integrative framework that links frugal innovation, creating shared value (CSV), and humanistic governance to cooperative performance, addressing a gap in cooperative governance research. Employing SmartPLS3 with conditional mediating (CoMe) analysis, data were collected from 342 fishermen across Java. Findings reveal that CSV significantly mediates the relationship between frugal innovation and cooperative performance, while humanistic governance positively moderates the CSV–performance link. This model offers empirical validation for applying corporate governance principles in cooperative settings. Theoretically, it advances understanding of how governance enhances value creation in social enterprises. For practitioners, the results underscore that strengthening humanistic governance is not merely ethical but strategic—leaders must cultivate participatory, value-driven governance to boost cooperative outcomes. This research marks an early empirical attempt to operationalize governance's conditional role in social business ecosystems.